Synthesis and structural properties of para-diselenopyrazines - Hüßler, Christopher; Dietl, Martin C.; Kahle, Justin; Lopes, Eric F.; Kawamura, Miku; Krämer, Petra; Rominger, Frank; Rudolph, Matthias; Hachiya, Iwao; Hashmi, A. Stephen K. (Chemical communications, 2024)
Recently, dithienopyrazines have emerged as promising building blocks in the field of materials science, showcasing their potential as hole-transport materials in organic electronic devices. Herein, we report the synthesis of its heavier analogues, the diselenopyrazines, along with an analysis of their optoelectronic and structural properties. In the acquired crystal structures, interesting molecular packing motifs suitable for potential device fabrication were observed. Additionally, short contact interactions are present in one of the investigated molecules.
Gesehen am 26.03.2024